Cyclic Sequential Removal of Alizarin Red S Dye and Cr(VI) Ions Using Wool as a Low-Cost Adsorbent - Khamis, Mustafa (2020)
Alizarin red S (ARS) removal from wastewater using sheep wool as adsorbent was investigated. The influence of contact time, pH, adsorbent dosage, initial ARS concentration and temperature was studied. Optimum values were: pH = 2.0, contact time = 90 min, adsorbent dosage = 8.0 g/L. Removal of ARS under these conditions was 93.2%. Adsorption data at 25.0 °C and 90 min contact time were fitted to the Freundlich and Langmuir isotherms. R2 values were 0.9943 and 0.9662, respectively. Raising the temperature to 50.0 °C had no effect on ARS removal. Free wool and wool loaded with ARS were characterized by Fourier Transform Infrared Spectroscopy (FTIR). ARS loaded wool was used as adsorbent for removal of Cr(VI) from industrial wastewater. ARS adsorbed on wool underwent oxidation, accompanied by a simultaneous reduction of Cr(VI) to Cr(III). The results hold promise for wool as adsorbent of organic pollutants from wastewater, in addition to substantial self-regeneration through reduction of toxic Cr(VI) to Cr(III). Sequential batch reactor studies involving three cycles showed no significant decline in removal efficiencies of both chromium and ARS.